Examination Under Anesthesia Improves Agreement on Mechanical Stability: A Survey of Experienced Pelvic Surgeons. Issue 7 (July 2021) - Tucker, Douglass; Carney, John; Nguyen, Aileen; Alluri, Ram K.; Lee, Adam; Marecek, Geoffrey
Abstract : Objectives: To assess agreement among experts in pelvic fracture management regarding stability and need for operative repair of lateral compression-type pelvic fractures with static radiographs compared to static radiographs and examination under anesthesia (EUA). Setting: Online survey. Patients/Participants: Ten patients who presented to our level-1 trauma center with a pelvic ring injury were selected. Vignettes were distributed to 11 experienced pelvic surgeons. Intervention: Examination under anesthesia. Main Outcome Measurements: Agreement regarding pelvic fracture stability and need for surgical fixation. Results: Agreement on stability was achieved in 4 (40%) cases without EUA compared to 8 (80%) cases with EUA. Interreviewer reliability was poor without EUA and moderate with EUA (0.207 vs. 0.592). Agreement on need to perform surgery was achieved in 5 (50%) cases compared to 6 (60%) cases with EUA. Interreviewer reliability was poor without EUA and moderate with EUA (0.250 vs. 0.432). For reference cases with agreement, surgeons were able to predict stability or instability using standard imaging in 57 of a possible 88 reviewer choices (64.8%) compared to 82 of 88 choices (93.2%) with the addition of EUA ( P < 0.0001). Conclusions: EUA increased agreement among experienced pelvic surgeons regarding the assessment of pelvic ring stability and the need for operative intervention. Further research is necessary to define specific indications for which patients may benefit from EUA. Abstract : Supplemental Digital Content is Available in the Text.